Analisa Manajemen Marketing dalam Meningkatkan Volume Penjualan PT. Dantosan Precon Perkasa - Tanjung, Boma Jonaldy; Handayani, Tantri (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2022)
In today's era of marketing is very influential in the development of a company, especially a company engaged in the field of Products and Services, it certainly makes a company rely heavily on the role of marketing is to increase the productivity of the company. One of the companies that need marketing role is PT. Dantosan Precon Perkasa, one of the companies engaged in the field of products and services requires a petrified figure marketing can develop products owned, the company manufactures precast concrete and possess marketing experience that can compete with other competitors in the field are the same, and marketing a very influential role in the sale of products and be able to continue to increase the volume of product sales increasing each time. PT. Dantosan Precon Perkasa is a company engaged in the field of products and services provide solutions for more rapid development and not discard or remove the cost is too great. By launching products that are useful for irrigation, construction of buildings, overpasses, fencing, etc., as well as providing important information on precast concrete. The conclusion of the research conducted by the authors showed that marketing is very influential figure for PT. Dantosan Precon Perkasa to increase the volume of sales of products owned, and can compete with other competitors kompetito-its, is evident from the increased sales levels each time, so the PT. Dantosan Precon Perkasa be a company to be reckoned with